Cytosolic phospholipase A2 in infiltrating monocyte derived macrophages does not impair recovery after spinal cord injury in female mice - Ethan P. Glaser; Timothy J. Kopper; William M. Bailey; Hassan K. Kashif; Reena Kumari; Andrew N. Stewart; John C. Gensel (Scientific Reports)
Abstract Spinal cord injury (SCI) leads to permanent motor and sensory loss that is exacerbated by intraspinal inflammation and persists months to years after injury. After SCI, monocyte-derived macrophages (MDMs) infiltrate the lesion to aid in myelin-rich debris clearance. During debris clearance, MDMs adopt a proinflammatory phenotype that exacerbates neurodegeneration and hinders recovery. The underlying cause of the lipid-mediated MDM phenotype shift is unclear. Our previous work suggests that cytosolic phospholipase A2 (cPLA2) plays a role in the proinflammatory potentiating effect of myelin on macrophages in vitro. Cytosolic phospholipase A2 (cPLA2) frees arachidonic acid from phospholipids, generating eicosanoids that play an important role in inflammation, immunity, and host defense. cPLA2 is expressed in macrophages along with multiple other cell types after SCI, and cPLA2 inhibition has been reported to both reduce and exacerbate secondary injury pathology recovery. The role of cPLA2 in MDMs after SCI is not fully understood. We hypothesize that cPLA2 activation in MDMs after SCI contributes to secondary injury. Here, we report that cPLA2 plays an important role in the myelin-induced inflammatory macrophage phenotype in vitro using macrophages derived from cPLA2 knockout bone marrow. Furthermore, to investigate the role of cPLA2 in MDMs after SCI, we generated female bone marrow chimeras using cPLA2 knock-out donors and assessed locomotor recovery using the Basso Mouse Scale (BMS), CatWalk gait analysis system, and horizontal ladder task over six weeks. We also evaluated tissue sparing and intralesional axon density six weeks after injury. cPLA2 KO chimeras did not display altered locomotor recovery or tissue pathology after SCI compared to WT chimera controls. These data suggest that although cPLA2 plays a critical role in myelin-mediated potentiation of proinflammatory macrophage activation in vitro, it may not contribute to secondary injury pathology in vivo after SCI.